Interaction of DNA Bases with Gold Substrates - Rosa, Marta; Sun, Wenming; Felice, Rosa Di (Journal of Self Assembly and Molecular Electronics, 2023)
The interaction of molecules with inorganic substrates is a crucial issue for applications in molecular electronics. It influences important factors such as the immobilization efficiency and the charge injection through the inter- face. Moreover, mechanical aspects connected to the unfolding of biological molecules are important. We hereby present recent efforts in our group to tackle these problems, based on density functional theory calculations. In particular, we discuss our results on the adsorption of cytosine on Au(111) and on the interaction of guanine, in its natural and size-expanded forms, with small Au clusters. We find that cytosine binds to the Au(111) surface with a mechanism that involves charge sharing, intermediate between chemisorption and physisorp- tion. The investigation of small complexes between guanine and gold clusters reveals the formation of hydrogen bonds: these configurations with unusual bonds are relevant at the corners of nanoparticles, while they can probably be neglected when DNA binds on flat extended metal surfaces.